Strategic Marketing Innovation in Startups: Navigating Uncertainty with Agility and Creativity - Mansur, Daduk Merdika (Manunggal Halim Jaya, 2025)
This research investigates the role of strategic marketing innovation in helping startups navigate uncertainty by leveraging agility and creativity. Amid the dynamic shifts brought about by globalization, technological advancement, and events such as the COVID-19 pandemic, startups are required to develop unique and adaptive marketing approaches to remain competitive and sustainable. The purpose of this study is to explore how agility the ability to respond rapidly to change and creativity the capacity to generate novel and valuable marketing solutions jointly influence strategic marketing innovation in startups. A descriptive quantitative method was applied to analyze patterns, effectiveness, and interrelations among agility, creativity, and marketing innovation in startups operating within dynamic sectors. Data were collected through structured surveys administered to startup founders and marketing professionals, and analyzed using correlation and regression techniques. The findings reveal that marketing agility significantly enhances startups’ ability to adapt marketing strategies in real time, while creativity contributes to differentiation, brand resonance, and consumer engagement. Moreover, the interaction between agility and creativity produces synergistic outcomes in terms of marketing innovation effectiveness. Digital capability and market sensing were found to moderate these relationships, further strengthening their influence on startup performance. The study concludes that strategic marketing innovation, supported by agile and creative capabilities, plays a critical mediating role in translating internal competencies into performance outcomes such as customer acquisition, brand positioning, and market responsiveness. This research provides theoretical and practical insights for startup founders, investors, and policymakers aiming to foster innovation and resilience in early-stage ventures.